1990
DOI: 10.1111/j.1365-2621.1990.tb06013.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Oils and α‐Tocopherol Supplementation on Membranal Lipid Oxidation in Broiler Meat

Abstract: The effects of different dietary oils and a-tocopherol on the fatty acid composition of mitochondrial and microsomal lipids of broiler muscle and their lability to NADPH-induced peroxidation were investigated. Fatty acid composition of both neutral lipids and phospholipids of mitochondria and microsomes was influenced by dietary oil composition. Supplementation of the diet with u-tocopherol only appeared to increase the a-tocophcrol concentration in the microsomal membranes in the dark meat. The rate of NADPH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
2
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 24 publications
4
50
2
6
Order By: Relevance
“…Compared with other meat, chicken meat is relatively abundant in PUFA, including the key n-3 fatty acids, and is easily attacked by free radicals (Asghar et al, 1990;Rhee et al, 1996). The reaction of 2-thiobarbituric acid with MDA is widely used for measuring the extent of oxidative deterioration of lipid in muscle foods .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other meat, chicken meat is relatively abundant in PUFA, including the key n-3 fatty acids, and is easily attacked by free radicals (Asghar et al, 1990;Rhee et al, 1996). The reaction of 2-thiobarbituric acid with MDA is widely used for measuring the extent of oxidative deterioration of lipid in muscle foods .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to chicken, Asghar et al (1989Asghar et al ( , 1990 found that supplementation of the diet with a-tocopherol Total a-tocopherol levels increased 1.6-and 1.8-fold increase in mitochondria and microsomes, respectively (70 vs. 250 mg/kg) Lauridsen and Jensen (2005) (200 mg/kg) only appeared to increase the a-tocopherol concentration in the microsomal membranes in the dark meat of chicken and did not increase, to any extent, the concentration of a-tocopherol in the mitochondrial fractions isolated from dark and white meat as compared to those isolated from the control group. In most of the experiments mentioned in Table 1, the differences in the concentrations of a-tocopherol in the subcellular fractions were evident in the enhanced oxidative stability of the enriched membranes, that is, reduced rates of Fe 2?…”
Section: Experiments With Muscle Membranes Isolated From Livestockmentioning
confidence: 99%
“…The turtle dove is essentially a granivorous bird that eats seeds of cereals, sunflower and wild species (Jime´nez, Hodar, & Camacho, 1992). The fatty acid composition of both glycerides and phospholipids in poultry meat is influenced by diet (Ahn, Wolfe, & Sim, 1995;Asghar, Lin, Gray, Buckley, Booren, & Flegal, 1990;Meyner, Genot, & Gandemer, 1999); thus, the fatty acid composition of thrush and turtle dove meat will probably be different.…”
Section: Introductionmentioning
confidence: 99%